'Right Action' and the environment: a common environmental catechism, fundamentalism, and political extremism. (4th August 2014) - Fitch, Eric J.
Examination of the major religions of the world points out to scholars an embedded common call for respect and stewardship of the Earth. It appears that it is only at the fundamentalist fringes of some of these faiths that this call is modified into one of exploitation. Although stewardship of the natural world is not always or even often central in the teachings of modern faiths, it is clearly there. Why then does it seem that even in outwardly religious countries such as the United States these supposedly foundational messages are ignored in light of economic, political and social imperatives? This paper will examine three key questions which may shed some light on these matters. First, what are the major religions of the United States and what are, if any, their identifiable core dogmas with regard to the natural environment? This is not an effort at syncretism, but rather that in the manner of identifying and listing commonly held beliefs amongst related and unrelated religions. Second, identification of outliers in the religious community; i.e., which if any religious sects go against the concepts of environmental stewardship? Third, what is the apparent influence of any of these religious belief systems on the socio–economic and political systems and decisions of the nation–state? Examples from past and present governments in public pronouncements and policies will be examined to see if there are discernible influences from professed beliefs.